Efficacy and Tolerability of Nintedanib in Idiopathic-Inflammatory-Myopathy-Related Interstitial Lung Disease: A Pilot Study - Liang, Junyu; Cao, Heng; Yang, Yang; Ke, Yini; Yu, Ye; Sun, Chuanyin; Yue, Lihuan; Lin, Jin (Frontiers in Medicine, 2021)
Objectives: To initially clarify the efficacy and tolerability of nintedanib in patients with idiopathic-inflammatory-myopathy-related interstitial lung disease (IIM-ILD). Methods: A retrospective, real-world analysis was conducted in IIM-ILD patients who regularly received outpatient visit or hospitalization from January 2018 to March 2020 in three centers. And the patients were divided into two groups depending on presence or absence of nintedanib therapy. Comparisons, Kaplan-Meier survival analysis and propensity score matching were made to identify difference in time to death from any cause, incidence of rapidly progressive interstitial lung disease (RP-ILD) and comorbidity of pulmonary infection between the two groups. The following logistic regression analyses and Cox proportional-hazard regression analyses were used to verify the therapeutic value of nintedanib as well as clinical significance of other factors. Adverse events were descriptively recorded. Results: Thirty-six patients receiving nintedanib therapy and 115 patients without use of nintedanib were included. Before and after propensity score matching, the primary comparisons revealed better survival (P=0.015, P=0016 respectively) and lower incidence of RP-ILD (P=0.017, P=0.014 respectively) in patients with nintedanib therapy. Logistic regression analysis identified that disease activity (P<0.001), Percent-predicted diffusing capacity of the lung for carbon monoxide (DLCO%, P=0.036), nintedanib therapy (P=0.004, OR value=0.072) and amyopathic dermatomyositis (ADM, P=0.012) were significantly correlated with RP-ILD. Cox proportional hazards regression analysis suggested that disease activity (P<0.001), anti-MDA5 antibody (P<0.001) and nintedanib therapy (P=0.013, HR value=0.268) were significantly associated with survival of IIM-ILD patients. Similar results can also be seen in analyses after propensity score matching. In the 36 patients with nintedanib therapy, diarrhea was the most common adverse event (44.4%) and hepatic insufficiency contributed to most dosage reduction (44.4% of nine patients) or therapy discontinuation (60.0% of five patients). Conclusions: Nintedanib was found to reduce incidence of RP-ILD and improve survival in IIM-ILD patients in a real-world setting. Anti-MDA5 antibody could be taken as a risk factor for unfavorable outcome. ADM was significantly correlated with occurrence of RP-ILD. In addition to the most frequent diarrhea, hepatic insufficiency was closely related to dosage reduction or therapy discontinuation.